Energy demand and costs of air conditioning system with recirculation and recuperator for a clean room - Maćkowiak , Monika; Porowski, Mieczysław (Instal, 2019)
The article presents an analysis of the unit demand for usable, final and primary energy as well as the unit costs of air conditioning system thermodynamic treatment with a cross-flow or counter-flow heat exchanger and air recirculation for a clean room of ISO7 class. As a tool in the optimization procedure, simulation model of the air conditioning system operation during the whole year was formulated and used, assuming two cases of relative humidity regulation: φp = 45% and φp = 40÷50%. It was also assumed two variants of the heat exchanger protection against frost: variant 1 – with electric pre-heater and variant 2 – with „by-pass” of the recuperator. Air changes in the simulation model were carried out in according to the algorithms of energy-optimal thermodynamic treatment. The calculation results show that the use of an electric pre-heater before the heat recovery exchanger allows to reduce the demand for primary energy by 8,8÷11%. It also allows to reduce the unit costs of thermodynamic air treatment by 6,4÷6,6% – depending on the relative humidity range of air in the room – relative to the use of a recuperator „by-pass”.